Memorable City Breaks in Serbia: Tourists' Sociodemographic Background - Tešin, Aleksandra; Kovačić, Sanja; Bratić, Marija (Turizam, 2025)
City breaks have become one of the most popular and rapidly expanding forms of travel. As a result, the market for these trips is becoming increasingly competitive. Due to major changes in tourist demand, it has become increasingly difficult to meet their needs. Many cities are still focused on providing classic tourism goods and services, ignoring travelers' growing desire for distinctive and unforgettable experiences. Such experiences are essential for the success of a tourist destination, achieving competitiveness, and determining tourists’ future behavior. Different people may perceive travel experience differently, which is determined by their personal background and demographics. However, the link between tourist sociodemographic features and MTEs has not been directly examined. Therefore, this study aimed at exploring the impact of tourists’ sociodemographic characteristics in shaping memorable experiences in city break destinations. The research was carried out among 614 international tourists in three Serbian cities. The findings revealed the impact of gender, age, marital status, income, and travel companions on MTEs.
Keywords: memorable tourism experience; city break; sociodemographic characteristics; tourists; Serbia